Factors and Types of Consumer Behaviour in the Food Market - НемковаЕкатерина Васильевна (Journal of Economic Sociology, 2010)
The aim of the paper is to reveal the main factors affecting the choice of food products, and the analysis of behaviour offood consumers. A standardized survey of adult population was conducted in Moscow and Tumen. The analysis of thedatabase (sample comprises 540 people) allowed to define four types of consumers: conservative, wasteful, impulsiveand inconsistent. The obtained results demonstrate that people are able to ‘switch’ between these types of consumption.